Harnessing the winds of change. Issue 1 (2nd January 2022) - Macduff, Anne; Holmes, Vivien
ABSTRACT: Emerging scholarship demonstrates that the curriculum can have a positive impact on student wellbeing. Indeed, a well-designed and delivered curriculum may serve a protective function, bolstering the wellbeing of students in the classroom when life outside is full of pressures and stressors. This is good news. It suggests that educators concerned about student wellbeing can make a positive difference by focusing on educational design principles and developing sound teaching practices. There are already a number of high-quality, web-based resources designed to assist educators in this task. One important issue yet to be explored concerns the barriers teachers experience in implementing curriculum change and how to overcome them. This article evaluates the effectiveness of a "Wellbeing in the Curriculum Tool" at an Australian law school. We argue that if we wish to improve law student wellbeing, the way that the message of change is delivered needs to be as enhancing of wellbeing as the content.